Effect of Traction Therapy in Knee Osteoarthritis: A Prospective Controlled Study - Şenay Özdolap; Selda Sarıkaya; Ülkü Koç; Aynur Başaran (Archives of Rheumatology, 2006)
Objective: To investigate the effect of traction therapy on knee osteoarthritis. Patients and Methods: Forty-three patients diagnosed knee osteoarthritis were included in this study. Knee radiographies of patients were taken and classified according to Kellgren-Lawrence classification. Twenty-four patients were treated with traction, hot pack, microwave and isometric exercises while 19 patients in control group were treated with hot pack, microwave and isometric exercises for 15 sessions. Traction was applied intermittently with 15 kg for 20 minutes while patients were sitting position, their legs fully extended. Range of motion of knee was measured with goniometry. The patient’s functional status was determined with Lequesne Functional Index and pain levels in rest and motion evaluated with visual analog scale (VAS) before and after 15 therapy sessions. Results: There was statistically significant decreasing in VAS (rest) (p<0.05), VAS( motion) (p<0.05) and Lequesne Funtional Index (p<0.05) in traction group. Conclusion: We suggest traction therapy has beneficial effects on pain and functional status in knee osteoartrhritis. (Rheumatism 2006; 21: 84-6)